Personality Functioning and Mentalizing in Patients With Subthreshold or Diagnosed Borderline Personality Disorder: Implications for ICD-11 - Rishede, Marie Zerafine; Juul, Sophie; Bo, Sune; Gondan, Matthias; Bjerrum Møeller, Stine; Simonsen, Sebastian (Frontiers in Psychiatry, 2021)
The 11th revision of the International Classification of Diseases for Mortality and Morbidity Statistics (ICD-11) defines personality disorder according to personality functioning, which relates to self- and interpersonal functioning. The aim of the present study was to assess the relationship between mentalizing and personality functioning in patients with subthreshold or diagnosed borderline personality disorder. A total of 116 eligible participants were included. Mentalizing was assessed using the Mentalization Questionnaire (MZQ), personality functioning (self- and interpersonal functioning) was assessed using the Level of Personality Functioning Scale-Brief Form 2.0 (LPFS-BF), and borderline severity was assessed using the Zanarini Rating Scale (ZAN-BPD). Mediation analysis was employed to test if mentalizing accounted for the relationship between borderline severity and self- and interpersonal functioning. We found a significant relationship between borderline severity and both subscales of the LPFS-BF. Mentalizing fully and significantly mediated the relationship between borderline severity and interpersonal functioning. However, mentalizing only partly mediated the relationship between borderline severity and self-functioning. Controlling for the covariates gender and age did not impact the results. Mentalizing is likely to be involved in the ICD-11 model of personality functioning, especially interpersonal functioning. This could emphasize the relevance of therapy aimed at strengthening mentalizing abilities when treating personality pathology in general and people with borderline personality disorder in particular. However, self-functioning may be more nuanced, as aspects other than mentalizing also influence self-function. The study is explorative in nature and has methodological limitations that require caution in the interpretation and generalizability.